AL-SAMĀ’: KAJIAN EPISTEMOLOGI ILMU NAHW - Muhammad Thoriqussu’ud (JURNAL PUSAKA, 2015)
Science nahw developed based on distinctive and unique methodological principles. According to Tammam Hassan, there are at least three methodological principles (the working procedure of the scientific establishment of nahw rules) namely; al-samÄ', al-istishhÄb, and al-qiyÄs. In the context of nahw, all-equal means a research procedure on a language events conducted by experts by seeking information from the original source to ensure its authenticity and thento be used as a theoretical basis. The term al-samÄ' is used in at least two contexts; First, the making or the usage of tenses is based on what is commonly used and heard directly from Arabs who rated fluent, for example mashdar samÄ'Ä«. Second, the usage of methods of nahw standardization rules through searching process, hearing, and recording directly from fushahÄ` al-â€˜arab.Keywords: Al-SamÄâ€™, Epistemologi, Nahw